Kiribati Health Financing System Assessment : Spend Better - World Bank Group (World Bank, Washington, DC, 2018)
This report identifies critical opportunities and constraints faced by the Kiribati health system as it makes progress towards Universal Health Coverage. Protecting the achievements that have been made over recent years, while continuing to improve a broader range of health outcomes, requires effective management of changes in financial and other institutional arrangements in the health sector. Despite notable improvements in recent decades, most population health outcomes in Kiribati do not compare well with other small countries in the Pacific. In many respects, this reflects the very difficult geographic, environmental and social determinants of health that the country faces. Strong collaboration across sectors is essential to implement the commitment to “health in all Government policies” agreed to in the Ambo Declaration in 2017. The Ministry of Health and Medical Services has taken impressive steps to improve its oversight of health sector performance. Continued attention to spending health dollars better is needed to achieve more efficient and quality outcomes from frontline service delivery, including for the outer islands.